Focal pyomyositis caused by Enterobacter in an immunocompetent patient: A case report - Haifa Tounsi; Mohamed Jlidi; Wafa Skouri; Sabrine Bachrouch; Zeineb Alaya; Emna Farhat; Siwar Sbaihi; Asma Bachalli; Raja Amri (SAGE Open Medical Case Reports, 2024)
Pyomyositis is a pyogenic infection of skeletal striated muscle, usually found in tropical areas, often in immunocompromised patients. We report a new observation of a nontropical Enterobacter pyomyositis occurring in an immunocompetent female in Tunisia. A 53-year-old patient presented with acute fever and intense myalgia in the right thigh. On clinical examination she had an altered general condition, a fever at 40°C and an important swelling of the lateral side of the right thigh. In biology, she had an inflammatory syndrome. Blood culture had identified Enterobacter. Muscle magnetic resonance imaging showed diffuse inflammatory involvement of the vastus lateralis muscle of the right quadriceps associated with edematous infiltration of subcutaneous fatty tissues. Diagnosis of pyomyositis was retained. Antibiotic therapy initially probabilistic and then adapted to the antibiogram was initiated with a favorable outcome. Although rare outside the tropics, the potential severity of pyomyositis encourages its better knowledge.